EFFECT OF PRE HEATER AND ECONOMIZER ADDITION ON ACID VALUE IN SPLITTING UNIT AT PT ENERGI OLEO PERSADA - Mubarak, Salman; Rahmawati, Cut Aja; Nurdin, Irwan (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT Temperature Problems and Stability of Fatty Acid Quality Become One of the Important Factors in the Occurrence of Hydrolysis in a Splitting Reactor Where Quality Instability Often Occurs in the Fat Splitting Hydrolysis Process, The Addition of Pre Heater and Economizer Provides a Significant Acid Value Stability Impact Judging From the Results of Analysis Conducted Within 12 Hours of Hydrolysis Process Time. With Several Temperature Variations Starting From 110 - 120 OC, Optimum Acid Value Conditions Are Obtained at 120 OC with the Maximum Acid Value Results at Acid Value 208.08. The combination of the addition of Pre Heater and Economizer can increase the efficiency of continuous steam use that can reduce production costs and ensure the stability of the temperature of the material that will enter the splitting reactor, the temperature can be varied to adjust the required heat needs in order to achieve a more perfect hydrolysis by considering economic aspects.Keywords: Preheater,Economizer, Acid Value, Hidrolisa, Splitting